Association between regular physical exercise and depressive symptoms mediated through social support and resilience in Japanese company workers: a cross-sectional study - Eisho Yoshikawa; Daisuke Nishi; Yutaka J. Matsuoka (BMC, 2016)
Abstract Background Regular physical exercise has been reported to reduce depressive symptoms. Several lines of evidence suggest that physical exercise may prevent depression by promoting social support or resilience, which is the ability to adapt to challenging life conditions. The aim of this study was to compare depressive symptoms, social support, and resilience between Japanese company workers who engaged in regular physical exercise and workers who did not exercise regularly. We also investigated whether regular physical exercise has an indirect association with depressive symptoms through social support and resilience. Methods Participants were 715 Japanese employees at six worksites. Depressive symptoms were assessed with the Center for Epidemiologic Studies Depression (CES-D) scale, social support with the short version of the Social Support Questionnaire (SSQ), and resilience with the 14-item Resilience Scale (RS-14). A self-report questionnaire, which was extracted from the Japanese version of the Health-Promoting Lifestyle Profile, was used to assess whether participants engage in regular physical exercise, defined as more than 20 min, three or more times per week. The group differences in CES-D, SSQ, and RS-14 scores were investigated by using analysis of covariance (ANCOVA). Mediation analysis was conducted by using Preacher and Hayes' bootstrap script to assess whether regular physical exercise is associated with depressive symptoms indirectly through resilience and social support. Results The SSQ Number score (F = 4.82, p = 0.03), SSQ Satisfaction score (F = 6.68, p = 0.01), and RS-14 score (F = 6.01, p = 0.01) were significantly higher in the group with regular physical exercise (n = 83) than in the group without regular physical exercise (n = 632) after adjusting for age, education, marital status, and job status. The difference in CES-D score was not significant (F = 2.90, p = 0.09). Bootstrapping revealed significant negative indirect associations between physical exercise and CES-D score through the SSQ Number score (bias-corrected and accelerated confidence interval (BCACI) = −0.61 to −0.035; 95 % confidence interval (CI)), SSQ Satisfaction score (BCACI = −0.92 to −0.18; 95 % CI), and RS-14 score (BCACI = −1.89 to −0.094; 95 % CI). Conclusion Although we did not find a significant direct association between exercise and depressive symptoms, exercise may be indirectly associated with depressive symptoms through social support and resilience. Further investigation is warranted.